When plants produce not enough or at all: metabolic engineering of flavonoids in microbial hosts - Trantas, Emmanouil A.; Koffas, Mattheos A. G.; Xu, Peng; Ververidis, Filippos (Frontiers in Plant Science, 2015)
Flavonoid metabolism and its fascinating molecules that are natural products in plants, have attracted the attention of industry and researchers involved in plant science, nutrition, bio/chemistry, chemical bioengineering, pharmacy, medicine, etc., since flavonoids were found to be directly or indirectly connected to health. Subsequently, in the last few years flavonoids became top stories in pharmaceutical industry, which is continually seeking for novel ways to produce safe and efficient drugs. Microbial cell cultures can act as workhorse bio-factories by offering their metabolic machinery for the benefit of optimizing the conditions and increasing the productivity of a selective flavonoid. Furthermore, metabolic engineering methodology came to reinforce what nature does best by tuning inadequacies and dead-ends of a metabolic pathway. Combinatorial biosynthesis techniques led to discovery of novel ways to produce plant natural and even unnatural flavonoids, while on top of that metabolic engineering gave the opportunity to industry to invest in synthetic biology to overcome restricted diversification and productivity issues existing so far in synthetic chemistry protocols. In this review, we present an update on rationalized approaches for the production of natural or unnatural flavonoids through biotechnology, analyzing the significance of combinatorial biosynthesis of agricultural/ pharmaceutical compounds produced in heterologous organisms. We also quote strategies and achievements thrived so far in the area of synthetic biology, with emphasis on metabolic engineering targeting the cellular optimization of microorganisms and plants producing flavonoids, stressing the advances in flux dynamic control and optimization. The involvement of the rapidly increasing numbers of assembled genomes that contribute to the gene- or pathway- mining to identify gene(s) responsible for producing species-specific secondary metabolites is finally considered.